Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.